Establishment of a Dihydrofolate Reductase Gene Knock-In Zebrafish Strain to Aid Preliminary Analysis of Congenital Heart Disease Mechanisms - Gong, Ke; Xie, Ting; Yang, Yifeng; Luo, Yong; Deng, Yun; Chen, Kun; Tan, Zhiping; Guo, Hui; Xie, Li (Frontiers in Cardiovascular Medicine, 2021)
Background: The dihydrofolate reductase (DHFR) gene is imperative in development, therefore it is essential to explore its effects on heart development. Thus, here a dhfr zebrafish knock-in (KI) strain was constructed. Methods: CRISPR/Cas9 technology was used to establish the dhfr KI zebrafish strain. This strain was hybridized with TgG fluorescent strain zebrafish to observe the phenotypes of heart shape, size, and circularization direction. Wild-type (WT) and KI zebrafish were then dissected and histologically stained to observe pathological changes. Western blot analysis was used to verify the increased expressions of zebrafish genes after KI. Hybridization experiments were used to confirm the presence of abnormal gonadal dysplasia. Results: The zebrafish dhfr KI strain was successfully constructed through CRISPR/Cas9 technology. At 6 days post fertilization (dpf), microscopic examinations of KI (homozygous) specimens revealed pericardial effusions, heart compressions, and curled tails. Compared with WT, the Hematoxylin and Eosin (H&E) tissue sections of KI-homozygous zebrafish showed defects such as reduced atria and ventricles. Western blot analysis indicated that the expression of the DHFR protein increased in both heterozygotes and homozygotes of dhfr KI zebrafish. Hybridization experiments revealed that dhfr KI may affect gonadal function. Conclusion: The DHFR gene plays an important regulatory role in the process of heart development, and copy number variations (CNVs) of this gene may constitute a new pathogenic mechanism of congenital heart disease (CHD).